A close-in planet orbiting giant star HD 167768. (7th December 2022) - Teng, Huan-Yu; Sato, Bun'ei; Kunitomo, Masanobu; Takarada, Takuya; Omiya, Masashi; Harakawa, Hiroki; Xiao, Guang-Yao; Liu, Yu-Juan; Izumiura, Hideyuki; Kambe, Eiji; Yoshida, Michitoshi; Itoh, Yoichi; et al.
Abstract: We report the detection of a giant planet orbiting the G-type giant star HD 167768 from radial velocity measurements using the High Dispersion Echelle Spectrograph (HIDES) at Okayama Astrophysical Observatory (OAO). HD 167768 has a mass of $1.08_{-0.12}^{+0.14}\, M_{\odot }$, a radius of $9.70_{-0.25}^{+0.25}\, R_{\odot }$, a metallicity of $[\mbox{Fe}/\mbox{H}]=-0.67_{-0.08}^{+0.09}$, and a surface gravity of $\log g = 2.50_{-0.06}^{+0.06}$ . The planet orbiting the star is a warm Jupiter, having a period of $20.6532_{-0.0032}^{+0.0032}\:\mbox{d}$, a minimum mass of $0.85_{-0.11}^{+0.12}\, M_{\rm {J}}$, and an orbital semimajor axis of $0.1512_{-0.0063}^{+0.0058}\:\mbox{au}$ . The planet has one of the shortest orbital periods among those ever found around deeply evolved stars (log  g < 3.5) using radial velocity methods. The equilibrium temperature of the planet is 1874 K, as high as a hot Jupiter. The radial velocities show two additional regular variations at 41 d and 95 d, suggesting the possibility of outer companions in the system. Follow-up monitoring will enable validation of the periodicity. We also calculated the orbital evolution of HD 167768 b and found that the planet will be engulfed within 0.15 Gyr.